High sensitivity carbon nanotube based electrochemiluminescence sensor array - Venkatanarayanan, Anita (2011)
Ink jet printed carbon nanotube forest arrays capable of detecting picomolar concentrations of immunoglobulin G (IgG) using electrochemiluminescence (ECL) are described. Patterned arrays of vertically aligned single walled carbon nanotube (SWCNT) forests were printed on indium tin oxide (ITO) electrodes. Capture anti-IgG antibodies were then coupled through peptide bond formation to acidic functional groups on the vertical nanotubes. IgG immunoassays were performed using silica nano particles (Si NP) functionalized with the ECL luminophore [Ru(bpy)(2) PICH(2)](2+)], and IgG labelled G1.5 acid terminated PAMAM dendrimers. PAMAM is poly(amido amine), bpy is 2,2′-bipyridyl and PICH(2) is (2-(4-carboxyphenyl)imidazo[4,5-f][1,10]phenanthroline). The carboxyl terminal of [Ru(bpy)(2) PICH(2)](2+) (fluorescence lifetime ≈682 ± 5 ns) dye was covalently coupled to amine groups on the 800 nm diameter silica spheres in order to produce significant ECL enhancement in the presence of sodium oxalate as co-reactant in PBS at pH 7.2). Significantly, this SWCNT-based sensor array shows a wide linear dynamic range for IgG coated spheres (10(6) to 10(12) spheres) corresponding to IgG concentrations between 20 pM and 300 nM. A detection limit of 1.1 ± 0.1 pM IgG is obtained under optimal conditions.